2020
DOI: 10.1128/msphere.00959-19
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Efflux Pump-Mediated Antiseptic Resistance in Staphylococcus aureus Suggests a Need for Greater Antiseptic Stewardship

Abstract: Staphylococcus aureus-associated infections can be difficult to treat due to multidrug resistance. Thus, infection prevention is critical. Cationic antiseptics, such as chlorhexidine (CHX) and benzalkonium chloride (BKC), are liberally used in health care and community settings to prevent infection. However, increased administration of antiseptics has selected for S. aureus strains that show reduced susceptibilities to cationic antiseptics. This increased resistance has been associated with carriage of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Currently, there is still poor understanding of whether transcription of these genes can be affected by antiseptic exposure and, in turn, confer antibiotic resistance (72,77). In a recent study, LaBreck et al showed that exposure to the QAC benzalkonium chloride induced a sustained 10-fold increase in qacA expression as well as a sustained 2-fold increase in norA expression in isogenic strains of S. aureus (77). Although suchlike effects have not been studied for CPC so far, it must be kept in mind that genetic determinants conferring resistance to antibiotics and antiseptics are often linked to each other and located on the same plasmids (72).…”
Section: Figmentioning
confidence: 99%
“…Currently, there is still poor understanding of whether transcription of these genes can be affected by antiseptic exposure and, in turn, confer antibiotic resistance (72,77). In a recent study, LaBreck et al showed that exposure to the QAC benzalkonium chloride induced a sustained 10-fold increase in qacA expression as well as a sustained 2-fold increase in norA expression in isogenic strains of S. aureus (77). Although suchlike effects have not been studied for CPC so far, it must be kept in mind that genetic determinants conferring resistance to antibiotics and antiseptics are often linked to each other and located on the same plasmids (72).…”
Section: Figmentioning
confidence: 99%
“…Several studies showed examples of reduced susceptibilities to QACs, occurring in natural, clinical, and industrial isolates and, to a lesser extent, in laboratory evolution experiments 9 , 14 16 . Reduced susceptibility to QACs is underpinned by acquiring mutations in genes that increase QAC efflux by upregulation of inherent multidrug-efflux pumps 17 or by acquiring specialized QAC efflux pumps via horizontal gene transfer 18 , 19 . In addition, strains that have been evolved towards decreased susceptibility show reduced expression of porins related to reduced QAC uptake 20 , 21 and changes in membrane structure or composition 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of a common antiseptic agent, chlorhexidine, may cause accidental or recurrent inflammatory and allergic reactions [ 48 ], while the use of polihexanide may display toxic effects to keratinocytes and lead to dermatitis in patients [ 49 ], and wound irrigation with octenidine dihydrochloride may result in severe complications, such as aseptic necrosis and chronic inflammation in penetrating hand wounds [ 50 ]. No such side effects were reported as a result of the studied peptide’s activities, and, additionally, increased microbial tolerance/reduced susceptibility towards chlorhexidine [ 51 ], octenidine [ 52 ] and polihexanide [ 53 ] has already been indicated.…”
Section: Discussionmentioning
confidence: 99%